1993
DOI: 10.1136/jcp.46.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Monotypic plasma cells in labial salivary glands of patients with Sjogren's syndrome: prognosticator for systemic lymphoproliferative disease.

Abstract: Aims: To determine the prevalence of plasma cell monotypia in labial salivary gland tissue of patients with and without

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
1
13

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 19 publications
0
20
1
13
Order By: Relevance
“…In this regard, evidence of B cell hyperactivity, including circulating immune complexes, hypergammaglobulinemia, and/or autoantibodies (especially those to the Ro/SSA and/or La/SSB autoantigens and rheumatoid factors), are frequently found in patients with primary SS (1,2). The lymphoid infiltrates of the inflamed glands, often resembling germinal center-like structures, also contain a substantial number of B cells and plasma cells (4,5). B cells have been documented to infiltrate the glandular duct epithelium and, thereby, to contribute to the characteristic pattern of chronic lymphocytic inflammation that is called lymphoepithelial (myoepithelial) sialadenitis (7).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In this regard, evidence of B cell hyperactivity, including circulating immune complexes, hypergammaglobulinemia, and/or autoantibodies (especially those to the Ro/SSA and/or La/SSB autoantigens and rheumatoid factors), are frequently found in patients with primary SS (1,2). The lymphoid infiltrates of the inflamed glands, often resembling germinal center-like structures, also contain a substantial number of B cells and plasma cells (4,5). B cells have been documented to infiltrate the glandular duct epithelium and, thereby, to contribute to the characteristic pattern of chronic lymphocytic inflammation that is called lymphoepithelial (myoepithelial) sialadenitis (7).…”
mentioning
confidence: 97%
“…In addition, there are several features of a systemic disease that may also involve additional organ systems (1,2). Although the glandular destruction has been shown to be mainly mediated by CD45ROϩ,CD4ϩ T lymphocytes (3), chronic B cell activation and proliferation seem to play an intimate role in both primary SS and its malignant complications (4)(5)(6). In this regard, evidence of B cell hyperactivity, including circulating immune complexes, hypergammaglobulinemia, and/or autoantibodies (especially those to the Ro/SSA and/or La/SSB autoantigens and rheumatoid factors), are frequently found in patients with primary SS (1,2).…”
mentioning
confidence: 99%
“…More recently, immunohistochemical and molecular studies have shown a high incidence of light-chain restriction in labial minor salivary glands (Bodeutsch et al, 1993;Speight and Jordan, 1993;Speight et al, 1994). In a large study of 70 labial glands from patients with Sjogren's syndrome, light-chain restriction was identified in 13 cases.…”
Section: Polyclonal and Monoclonal Gammopathies In Sjogren F S Syndromementioning
confidence: 99%
“…CD8+ T-lymphocytes with cytotoxic activity, characterized by their expression of granzymes constitute around 10 % of infiltrating cells. B cells, plasma cells (PCs) and macrophages (mØs) are the remaining infiltrating cells in exocrine tissues [3][4][5]. The presence of T and B cells, mØs and dendritic cells (DCs) varies according to the severity of the lesion [6].…”
mentioning
confidence: 99%